PENENTUAN SKALA PRIORITAS DALAM STRATEGI PEMASARAN PRODUK MEREK PECANDU COFFEE - Ragil Pardiyono; Susi Nugrahati (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
This study aims to design a priority marketing strategy using a marketing mix model by measuring consumer perceptions to increase sales volume.. From the Factor Analysis processing, there are 12 latent variables that have eigenvalues 1, namely product, service, public facilities, access, branding promotion, strategic, unique serving consumers, advertising media, lighting, entertainment, and quality. After that, it is processed using the Analytical Hierarchy Process (AHP), and the result is that there are 3 priority factors, namely the quality factor (31.66%), product (13.10%), and advertising media (11.93%). The quality factor strategy includes making SOPs, attending seminars / training, making P-IRT certifications, and making business licenses. Product factor strategy includes adding variant origin, redesigning the packaging. Marketing strategy through advertising media with Facebook and Instragram, becoming a merchant at Go-Food and Grab-Food, and partnerships with online payment application providers.